Nghiên cứu hiệu ứng tăng cường chiết của các nguyên tố đất hiếm nhẹ (La, Nd, Sm, Eu) bằng hỗn hợp triphenylphotphin oxit (TPPO) và axit 2-etyl hexyl 2-etyl hexyl photphonic (PC88A) từ dung dịch axit nitric - Đại và cộng sự, Lưu Minh (Vietnam Journal of Chemistry, 2014)
The extraction of rare earth elements (La, Nd, Sm, Eu) by mixture of triphenylphosphin oxide and 2-ethylhexyl 2-ethylhexyl phosphonic acid from nitric acid solutions has been developed. The influence of various factors such as the nitric acid concentrations, triphenylphosphin oxide/2-ethylhexyl 2-ethylhexyl phosphonic acid ratio,... on the Sk has been reported.